Still disease with persistent atypical dermatomyositis-like skin eruption with macrophage activation syndrome: a rare presentation - Kaushal, Shagun; Chauhan, Jatin (International Journal of Contemporary Pediatrics, 2025)
Still’s disease is a type of inflammatory arthritis that causes fevers, rashes, and inflammation of joints and, sometimes, internal organs. Still’s is also called systemic-onset juvenile idiopathic arthritis (SJIA), as it was first diagnosed in children. SJIA is a type of juvenile idiopathic arthritis (JIA), a group of arthritis conditions affecting children. JIA is one of the most common pediatric chronic diseases, with a prevalence rate varying from 3.8 to 400 cases/100,000 children, and a yearly incidence between 1.6 and 23 new cases for 100,000 children. SoJIA when considered as a JIA subtype includes about 10–20% of all JIA patients, but the percentage is higher in some countries and when only severe cases are considered. Indeed, in parts of Asia, it may account for up to 30–40% of all JIA cases. Here we report a case of Still’s disease in pediatric patient with a persistent atypical dermatomyositis like skin eruption complicated by MAS, highlighting diagnostic challenges and management strategies.